Impact of the Karma Yoga Practices Adopted by the Teachers in Higher Education on their Transformational Leadership Behaviour- A Study in Selected Universities of Delhi-NCR - Ms. Divya Sharma, Prof.(Dr.) S.K.Dhameja (International Journal of Advanced Science and Technology, 2020)
Today’s generation ofstudents see universities as a means to prepare for a well paid job rather than their overall personality development or enrichment of value system. So there is need of teachers who can improve the student’s academic experience by providing them transformational leadership. Also a teacher should be the believer of karma yoga and should practice selfless teaching methods and ideology. This study focuses on importance of Transformational Leadership and karma yoga characteristics among the educators of higher education in India also to determine the relationship between karma yoga and transformational leadership characteristics among the teachers of various universities of Delhi-NCR. Its main objective is to test the hypothesis that there exists significant positive impact of the karma yoga practices adopted by the teachers in higher education on their transformational leadership behaviour. Transformational Leadership comprises of four factors— idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration as identified by Bass (1998) and karmayoga comprises of four factors- significance of work, successful work, detachment from work and setting an example developed by Menon & Krishnan, (2004).These factors are included in questionnaire in the form of twenty six statements to measure the transformational leadership and karmayoga characteristics of the teachers and to identify the relationship between the two. The sample comprised of 461 faculties of various central, state and private universities of Delhi-NCR. The covariance based structural equation modelling is used to examine the hypothesis framed in the paper. The multiple regression model is also applied in order to examine the relationship between transformational leadership and its determinants. Findings reveal that the p value of the critical ratio is 9.687 which indicate the significant impact of karma yoga on the transformational leadership. Thus the hypothesis is accepted